The effect of the pheromones of male Awassi sheep and Shami goats on the secretion of luteinizing hormone (LH) and the growth of ovarian follicles in Awassi ewes during the reproductive season. - حربا, حسن; محمد موسى,; معتز زرقاوي , (Latakia University Journal -Biological Sciences Series, 2024)
The research aims to determine the effect of the pheromones of male Awassi sheep and Shami goats on the secretion of luteinizing hormone (LH) and the growth of ovarian follicles in Awassi sheep ewes during the reproductive season. The study was conducted on three groups of equal number n = 17 (during the reproductive season): The first group (Awassi ram wool extract), 15 ml of ram wool extract was placed on a piece of gauze and placed inside a mask specially designed for the experiment to be placed and fixed directly on the nose. The second group (Shami goat hair extract), 15 ml of goat hair extract was placed on a piece of gauze and placed inside a mask specially designed for the experiment to be placed and attached directly to the nose, and the third group (Awass rams). Calibration of LH was performed immediately before starting the treatment and 1, 10, and 20 hours after the treatment was applied. The ovaries of five ewes, randomly selected from each group, were examined from 0-24-48 hours after the end of treatment using an ultrasound device. The follicles were divided according to their diameter into small follicles with diameters less than 3 mm, medium follicles whose diameters ranged from 3 to 6 mm, and large follicles with diameters greater than 6 mm. The results showed a direct and clear increase in LH concentrations after the start of the experiment in females in the study groups. The results also showed that follicle growth and maturation began immediately after applying the treatment in the experimental groups. It is concluded from this study that the pheromones extracted from the wool of rams and the goats of Shami goats had a better effect in stimulating the response of female Awassi sheep, which paves the way for their use as a substance in reproductive management in Awassi females.